A compact dual band short ended metamaterial antenna with extended bandwidth. Issue 5 (1st March 2016) - Gupta, Ashish; Kumar Chaudhary, Raghvendra
ABSTRACT: A compact dual‐band CPW–fed metamaterial inspired antenna using Composite Right/Left Handed (CRLH) resonant approach is presented in this article. The antenna is designed such that it can be operated in series resonant mode where resonance behavior is characterized by series LC parameters. Proposed antenna comprises two annular ring resonators connected with the signal patch intended to excite the higher order modes. This results extension of second band from 51.4% ( fc = 6.92 GHz) to 69.2% ( fc = 7.35 GHz). In addition to that proposed antenna shows compact nature with an electrical size of 0.14 λ0 × 0.21 λ0 × 0.01 λ0 at f0 = 2.18 GHz. The antenna is operating over 2.14–2.23 GHz, 4.81–9.90 GHz with simulated peak gain of 0.66 and 4.44 dB, respectively. Simulated radiation efficiencies of proposed antenna are 69.8 and 94.1% throughout first and second band, respectively. To examine the resonance and radiation characteristics prototype is fabricated and measured. Observed experimental results are in good agreement with those simulated one. These characteristics makes this antenna is a good candidate for modern wireless communication systems such as Bluetooth, WLAN/Wi‐Fi band. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:435–441, 2016.